Effects of Different Sources and Levels of Selenium on Performance, Thyroid Function and Antioxidant Status in Stressed Broiler Chickens - Fan, Chun; Yu, Bing; Chen, Daiwen (International Journal of Poultry Science, 2009)
The effects of adding different sources and levels of selenium on performance, thyroid function and antioxidant status in stressed broiler chickens were evaluated. Stress was induced by supplementation with 20 mg/kg Corticosterone (CORT) in basal diet. Total 144 Avian broilers were used for 2 weeks from 14 days of age, which were randomly distributed to 6 groups. One of these groups was fed with basal diets and the remaining with basal diet supplemented with CORT. Meanwhile, diets used in CORT groups were supplemented with 0, 0.1 or 0.4 mg/kg sodium selenite or yeast selenium, respectively. The results showed that dietary CORT resulted in significant suppression of growth and thyroid function, increase in creatine kinase activity and uric acid concentration in serum, indicating that CORT induced stress of broilers. In addition, the balance between pro-oxidants and antioxidants was disturbed by CORT administration, resulting in oxidative injury in the body. Supplementation of dietary selenium improved feed efficiency, promoted conversion of thyroxine (T4) to triiodothyronine (T3), minimized the changes of blood biochemical parameters; furthermore, it elevated antioxidases activities and decreased lipid peroxidation products in stressed broilers. The effects of adding 0.4 mg/kg selenium were better than 0.1 mg/kg. Although there was no significant difference between two selenium sources, it was conclude that high level of inorganic or organic selenium was able to attenuate stress and oxidative injury due to exogenous CORT administration, especially organic yeast selenium.